1989
DOI: 10.1017/s0022029900029241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of udder preparation on transmission of Staphylococcus aureus while milking with a multi-valved cluster

Abstract: With two groups of 12 cows, a procedure involving foremilking, teat washing and drying before milking was compared with no premilking preparation for its effects on mastitis and teat contamination. Half the cows in each group were deliberately infected in a single udder quarter with Staphylococcus aureus and milked alternately with uninfected cows for 9 weeks. To minimize transfer during milking all cows were milked with the use of a multi-valved claw.Five new staphylococcal infections developed in the 12 anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…2004; Magnusson et al. 2006), whilst other work has shown limited effect (Grindal and Bramley 1989). Different cleaning regimes vary in their effectiveness in reducing teat microbial levels.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…2004; Magnusson et al. 2006), whilst other work has shown limited effect (Grindal and Bramley 1989). Different cleaning regimes vary in their effectiveness in reducing teat microbial levels.…”
Section: Introductionmentioning
confidence: 96%
“…The objective of teat cleaning and udder hygiene is to enhance milk quality and aid in the control of mastitis (Galton et al 1984;Pankey 1989). Various studies have shown that premilking teat disinfection is beneficial (Galton et al 1986;Rasmussen et al 1991;Oliver et al 1993;Skrzypek et al 2004;Magnusson et al 2006), whilst other work has shown limited effect (Grindal and Bramley 1989). Different cleaning regimes vary in their effectiveness in reducing teat microbial levels.…”
Section: Introductionmentioning
confidence: 99%
“…Machine milking may also be considered as a major cause of bacterial cross contamination from cow to cow. However, a good premilking hygiene routine can decrease the cow infection ratio by not only reducing udder bacterial contamination from the environment, but also reducing bacterial contamination from other infected animals [9,12,11]. Newbould [21].…”
Section: Introductionmentioning
confidence: 99%
“…Nonspecific mastitis Specific mastitis The teat disinfection is applied to control IMI and enhance milk quality (Oliver et al, 2001) Various researchers have shown that pre milking teat disinfection is beneficial (Rasmussen et al, 1991, Oliver et al, 1993, Magnusson et al, 2006and Hillerton et al, 2007. However, other workers have shown its limited effect (Grindal and Bramley 1989, Singh 2015and Rowe et al, 2018. The present study included assessing the advantage of pre and post milking teat disinfection over post milking teat disinfection alone.…”
Section: Microbial Pathogen Not Detectedmentioning
confidence: 98%